Problems of the chidren's traumatism: structure, dynamics of types during the long-time follow-up - V. N. Mikhalchuk; S. O. Bondar (Kazimierz Wielki University, 2017)
There are presented the results of studying the structure of children's traumatism, dynamics of its variable types during 1999 -2016 inUkraineand Kirovogradska Oblast. The peculiarities by the character of changes in indices and their intensity with years were defined.